EARLY PLANNED BIRTH: A BETTER WAY TO MANAGE PRE-LABOR RUPTURE OF MEMBRANES AT TERM - Gul, Sehrish; Jamil, Mahwash; Basharat, Ayesha; Khan, Muhammad Aleem (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare mean pre-labour rupture of membranes (PROM)-delivery time, hospital stay, frequency of caesarean section and fetal distress associated with immediate induction versus expectant management with delayed induction in women presenting with pre-labour rupture of membranes at term. Study Design: Quasi-experimental study. Place and Duration of Study: Gynae/Obs. Unit of Shifa International Hospital, Islamabad, from Sep 2013 to Mar 2014. Methodology: A total of 294 pregnant females with gestational age between 37-41 weeks with singleton pregnancies and cephalic presentation presenting with pre-labour rupture of membranes were enrolled and equally distributed to two groups. Group A females were immediately induced with 50 micrograms of misoprostol per vaginally and group B was managed expectantly for 12 hours followed by labor induction with 50 micrograms of misoprostol per vaginally if labor did not ensue spontaneously in 12 hours. Results: Mean pre-labour rupture of membranes to delivery time was significantly shorter in immediate induction group when compared to the expectant group with delayed induction (6.93 ± 2.43 versus 19.25 ± 5.38 hours, p=0.001). Frequency of hospital stay of >3 days was also significantly lower in immediate induced group (29.9% n=44/147 versus 40.1% n=59/147, p=0.036). Higher percent-age of caesarean section (53.7% n=79/147 versus 44.9% n=66/147, p=0.129) and fetal distress (46.3% n=68/147 versus 38.8% n=57/147, p=0.129) were observed in immediate induction group. Conclusion: The mean pre-labour rupture of membranes to delivery interval and hospital stay was significantly less in immediate induction when compared to expectant management with delayed induction group. Rates of caesarean sections and...................